Improving Depression Screening in Underserved Populations in a Large Urban Academic Primary Care Center: A Provider-Centered Analysis and Approach. (July 2020) - Henry, Tracey L.; Schmidt, Stacie; Lund, Maha B.; Haynes, Tamara; Ford, Darby; Egwuogu, Heartley; Schmitz, Stephanie; McGregor, Brian; Toomer, Linda; Bussey-Jones, Jada
Screening for depression is paramount to identify patients with depression and link them to care, yet only 29% of patients in the primary care center (PCC) were screened for depression in 2016. A baseline survey identified provider barriers to depression screening, including lack of time, support staff, and referral resources. The purpose of this project was to increase depression screening in the PCC using the Patient Health Questionnaire (PHQ-2/9). The authors created an educational program for staff and providers that included referral resources, treatment guidelines, and a decision-support tool in the electronic medical record. A retrospective chart review was performed, from January 2016 to June 2017, to determine the percentage of patients who received annual depression screening. During the program, the PCC saw an increase in depression screening rates. Thus, it is possible to overcome barriers to depression screening in a primary care setting by providing resources and education to clinicians.